M127. BODY MASS INDEX IN THE MIDDLE-AGED OFFSPRING OF PARENTS WITH SEVERE MENTAL ILLNESS - Protsenko, Maria (Schizophr Bull, 2020)
BACKGROUND: The prevalence of obesity is increasing public health problem with significant costs. Elevated risk for obesity is reported in patients with severe mental illness. People with obesity have an increased risk for a number of common medical conditions, including type 2 diabetes, cardiovascular disease, coronary heart disease, dyslipidemia and hypertension. The increased physical illness may be associated with unhealthy lifestyles such as smoking, substance use, often with inadequate access to health services. Still, very is known about the comorbidity of SMI and obesity in families. We explored the association between parental severe mental illness and BMI in middle-aged offspring. Our hypothesis was that offspring of people with severe mental illness have increased risk for obesity. METHODS: The Northern Finland Birth Cohort 1966 is cohort study of offspring with expected date of birth in 1966. The final study sample included 5,467 middle-aged offspring. We used parental severe mental illness as exposure in the study. BMI measured.at the age of 46 years was classified in for categories: underweight (BMI below 18.5), normal range (BMI 18.5–24.9), overweight (BMI 25.0–29.9), obese class I (BMI 30.0–34.9) and obese class II-III (BMI 35 or more). We used mothers’ marital status, smoking, educational level and offspring’ place of birth as confounders. RESULTS: Risk for obesity was elevated in offspring of mothers with SMI (overweight: adjusted OR 1.81 (1.25–2.63), obese class I: 1.71 (1.08–2.73), obese class II-III: 2.36 (1.35–4.13)). For offspring of fathers with SMI the results were not statistically significant (overweight: adjusted OR 0.94 (0.70–1.26), obese class I: 1.42 (1.00–2.00), obese class II-III: 0.89 (0.51–1.56)). DISCUSSION: According to our knowledge, this is the first study of BMI in adult offspring of parents with severe mental illness. We found an elevated risk of obesity in the middle-aged offspring of mothers with SMI. The findings support our hypothesis of higher morbidity from obesity in offspring of parents with SMI. We found an elevated risk of substantially increased BMI in the middle-aged offspring of mothers with SMI. However, we did not find elevated risk of increased BMI in the middle-aged offspring of fathers with SMI and when examining the offspring of either parent with SMI. This means that there might be a common familial pathway leading to co-occurrence of obesity and SMI.